The impact of online educational service quality on the reputation of Dubai University during the COVID-19 pandemic from the perspective of students - Elomari, Abdelmuttaleb Abdelsalam (Journal of Educational and Psychological Sciences, 2025)
This study aimed to investigate the impact of online educational service quality on the reputation of Dubai University during the COVID-19 pandemic from the perspective of students. The researcher used a descriptive-analytical method and distributed a questionnaire to a sample of 77 students from Dubai University in the United Arab Emirates. The study found that the overall mean score for the level of online educational service quality on the reputation of Dubai University during the COVID-19 pandemic was 3.71, indicating a high level of satisfaction. The mean score for the domain of "educational service quality" was 3.82, also with a high rating. The mean score for the domain of "Dubai University reputation during COVID-19 pandemic" was 3.54, showing a high rating as well. The results also revealed no statistically significant differences in the total questionnaire score based on variables such as gender, major, and academic year. Additionally, the study indicated a positive effect of online educational service quality on the reputation of Dubai University during the COVID-19 pandemic. The study recommends generalizing the experience of Dubai University during crises and pandemics to other universities worldwide, while continuing to update and develop the university’s online service platforms and comprehensive educational resource websites for all academic disciplines.